Modern demographic processes in urban areas of the Republic of Kazakhstan - Nyussupova Gulnara; Sarsenova Indira (Bulletin of Geography. Socio-Economic Series)
The result of the growth in cities’ population is the migratory and natural movement of the population. Special attention is given in this article to the research of natural movement of the population of cities of Kazakhstan; this indicator of natural movement of the population is defined by the demographic processes in the future. Therefore, the given information about the natural and mechanical movement of the population can be considered as the original generalizing indicators of the processes that happen in population movement.